The Red Bull Paranauê from a Folkcomunicacional perspective:reflections on heritage, identity and competition (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT We consider the processes of globalization (ORTIZ, 2013, 2009) and the media and marketing appeals that shape the current circumstances in which culture and the market intersect. Therefore, it is reflected on the Red Bull Paranauê sporting event, held in Brazil in 2017 and 2018, highlighting Capoeira as Intangible Heritage and the projection built by the sports competition. Based on the folkmarketing conception (LUCENA FILHO, 2007), the implications of Red Bull Paranauê on identity and culture aspects are discussed. There are also voices of capoeiristas who stand in different ways on the phenomenon of the globalization of Capoeira and its media projections. While recognizing a certain worldwide visibility of Capoeira and Brazilian capoeiristas, it is concerned with the future effects of an exclusively competitive perspective. KEY-WORDS Capoeira; Red Bull Paranauê; Folkmartketing; Intangible assets; Identity.